Heart Angiotensin-Converting Enzyme and Angiotensin-Converting Enzyme 2 Gene Expression Associated With Male Sex and Salt-Sensitive Hypertension in the Dahl Rat - Ytrehus, Kirsti; Ludvigsen, Stian; Mancusi, Costantino; Gerdts, Eva; de Simone, Giovanni (Frontiers in Physiology, 2021)
Angiotensin converting enzyme 2 (ACE 2) in the heart including its sex dependency in the hypertensive heart, has not been much studied compared to ACE. In the present study, we used the Dahl salt sensitive rat exposed to fructose and salt to model a hypertensive phenotype in males, females and ovariectomized females. Blood pressure was measured by the tale cuff technique in the conscious state. Expression of RAS related genes ACE, ACE2, angiotensin II receptor type 1, Mas1 and CMA1 in the heart were quantified and results revealed significant differences between males and females with and without intact ovaries. The main results demonstrated were the presence of a male preponderance above both female groups for increase in ACE as well as ACE2 gene expression. The results are in accordance with a role of androgens or male chromosomal complement in controlling expression of the two ACE genes.